Brasileirinidae, a new isopod family (Crustacea: Isopoda) from the cave in Bahia (Brazil) with a discussion on its taxonomic position - Prevorčnik, Simona; Ferreira, Rodrigo Lopes (Zootaxa, 2012)
The aquatic troglobiont Brasileirinho cavaticus (Crustacea: Isopoda: Calabozoidea), new genus and species is described from the karst cave of the State of Bahia, Brazil. Based on its unique pleonal features i.e. the total absence of female pleopods I–II, uniramous male pleopods I–II, minute, uniramous respiratory pleopods III–V in both sexes and pleotelson not exceeding 45% of the pleon length, a new family, Brasileirinidae, is created. Some biological, ecological and behavioral data for the species are provided together with the nature conservation issues. Additionally, an assignment of the new species to the suborder Calabozoidea is discussed through comparison with the other two calabozoid species, Calabozoa pellucida and Pongycarcinia xiphidiourus. For the latter species, some previously missing morphological details, as well as a new locality record, are provided. According to the updated morphological evidence, the previously assumed relationships of Calabozoidea are discussed and, consequently, the diagnostic characters of some taxa emended.